Integrating single-cell RNA-seq, bulk RNA-seq and network pharmacology reveals protective effect of salidroside in peritoneal dialysis-associated peritoneal fibrosis - Li, Shuting; Ji, Yue; Zhu, Silin; Liu, Mi; Luo, Dan; Luo, Qimei; Mo, Min; Long, Haibo; Peng, Fenfen; Jia, Zhanjun; Dou, Xianrui (Frontiers in Pharmacology, 2025)
Salidroside (2- (4-Hydroxyphenyl) ethyl β-D-glucopyranoside, SAL) is a bioactive compound present in Rhodiola rosea L., exhibiting diverse pharmacological properties such as anti-inflammatory and anti-fibrotic effects. Despite its known benefits, the therapeutic potential of SAL in peritoneal dialysis (PD) -induced peritoneal fibrosis remains unexplored. This study aims to investigate the protective effects of SAL in PD-related peritoneal fibrosis and its underlying mechanisms through the integration of single-cell RNA-seq, bulk RNA-seq, and network pharmacology analyses. A total of 249 disease targets were identified through single-cell RNA-seq and bulk RNA-seq analyses. Functional enrichment analysis highlighted the involvement of extracellular matrix organization, neutrophil degranulation, and the vitamin D receptor (VDR) pathway in peritoneal fibrosis. By intersecting 148 drug targets with the 249 disease targets, four therapeutic targets for SAL treatment against peritoneal fibrosis were pinpointed: cathepsin S, VDR, plasminogen activator urokinase, and galectin 3. In a murine model of peritoneal fibrosis induced by intraperitoneal injection of 4.25% PD fluid, SAL treatment significantly mitigated peritoneal fibrosis, as evidenced by reduced collagen deposition, decreased protein expression of α-smooth muscle actin and Collagen I, and a thinner peritoneum. In vitro experiments demonstrated that SAL treatment inhibited extracellular matrix deposition, potentially through upregulation of VDR expression. In conclusion, SAL may target VDR domains as a therapeutic agent for PD-related peritoneal fibrosis. These findings comprehensively identify potential therapeutic targets for SAL in combating peritoneal fibrosis, providing a theoretical basis for the clinical application of SAL in the treatment of peritoneal fibrosis.